2021
DOI: 10.2147/phmt.s299202
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Birth Weight and Associated Factors Among Mother-Neonate Pairs in Public Hospitals, North Wollo, Ethiopia

Abstract: Background Birth weight or size at birth is an important indicator of the child’s vulnerability to the risk of childhood illnesses and diseases. Low birth weight is closely associated with fetal and neonatal morbidity, inhibited growth and cognitive development, and chronic diseases in life. The study was aimed to assess the birth weight of neonates and associated factors among mothers who gave birth at a public hospital in North Wollo, 2020. Methods A hospital-based cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
(27 reference statements)
1
15
0
Order By: Relevance
“…Female sex of child was statistically significant factor for higher odds of LBW, this finding supported by other studies in Jordan and Ethiopia [18,28]. The relationship may result from male fetuses being expelled later than female fetuses, so that males are more likely to be macerated [29].…”
Section: Discussionsupporting
confidence: 81%
“…Female sex of child was statistically significant factor for higher odds of LBW, this finding supported by other studies in Jordan and Ethiopia [18,28]. The relationship may result from male fetuses being expelled later than female fetuses, so that males are more likely to be macerated [29].…”
Section: Discussionsupporting
confidence: 81%
“…16 This is also in line with a study conducted in Ethiopia, where the prevalence of low birth weight was 24%. 2 Meanwhile, other studies showed lower prevalence of LBW, 9.7% 17 , 12.9% 18 , and 11.9% 19 respectively.…”
Section: Discussionmentioning
confidence: 92%
“…1 Birth weight predicts the child's overall development and chances of survival. 2 World Health Organization (WHO) defines low birth weight (LBW) as the weight of newborns less than 2500 grams irrespective of their gestational age. 3 LBW can be further subcategorized as very low birth weight (VLBW), which is under 1500 grams, and extremely low birth weight (ELBW), which is under 1000 grams.…”
Section: Introductionmentioning
confidence: 99%
“…In contrary to that, there are studies which showed high prevalence of LBW. Studies from different areas revealed that the prevalence of LBW at Adwa General Hospital, Northern Ethiopia was 10%(5), 9.4% at Southeast of Iran(12), 14.9% in Northwest part of Ethiopia(13), 15.8% at Wolaita Sodo University Teaching and Referral Hospital, Southern Ethiopia( 14), 18% at Kambata-Tembaro zone, southern Ethiopia(15), 20.73% in Central region of India( 16), 21% at Dire Dawa City, Eastern Ethiopia (17), and 24% at public hospital in North Wollo Zone, Amhara region Ethiopia (25). The variation in prevalence rate of low birth weight might be due to the variation in study area, study time, study sample size, infrastructure for health care, awareness, accessibility of health institution, and so on.…”
Section: Discussionmentioning
confidence: 99%